Diseño de una prensa neumática para elaborar puertas entamboradas. - Hernández Angamarca, Stalin Paúl (2015)
This thesis project comprises the "Design of a pneumatic press to make entamboradas doors." In this work a basic methodology for selecting the necessary components comprising the press, in order to obtain adequate design parameters is presented. During the research process was determined not desirable to design complex elements, taking advantage of the geometry of the profiles that make up the bed of the pneumatic press for making entamboradas doors. Proceeded to analyze the structure to determine the stresses produced by the actuators and observe the possible deformations that could present the pneumatic press for making entamboradas doors. In the control level switches that send a signal to govern the input and output shaft of the cylinders are used. Proceeded to perform the corresponding analysis in welded joints so with the calculations have a machine that works in good condition and shows no setback in its possible construction, calculation of the strength of advance and retreat of the pneumatic cylinders is performed, also proceeded to calculate the air consumption and the diameter of this pipe pneumatic system. Building a basic engineering prototype would be desirable, but is subject to funding, so one might consider building the prototype but this is optional.